2016
DOI: 10.1212/wnl.0000000000002436
|View full text |Cite
|
Sign up to set email alerts
|

Urinary LRRK2 phosphorylation predicts parkinsonian phenotypes in G2019S LRRK2 carriers

Abstract: Objective: To test whether phosphorylated Ser-1292 LRRK2 levels in urine exosomes predicts LRRK2 mutation carriers (LRRK21) and noncarriers (LRRK22) with Parkinson disease (PD1) and without Parkinson disease (PD2).Methods: LRRK2 protein was purified from urinary exosomes collected from participants in 2 independent cohorts. The first cohort included 14 men (LRRK21/PD1, n 5 7; LRRK22/PD1, n 5 4; LRRK22/PD2, n 5 3). The second cohort included 62 men (LRRK22/PD2, n 5 16; LRRK21/PD2, n 5 16; LRRK21/PD1, n 5 14; LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
131
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 17 publications
7
131
1
Order By: Relevance
“…The G2019S mutation in the activation loop of the kinase domain produces a ~3–5 fold effect in some models and clinical samples(Fraser et al, 2016a), and the mutation is well-known to be incompletely penetrant in the Ashkenazi Jewish population (e.g., ~20–30% lifetime risk for PD)(Marder et al, 2015). The Y1699C variant and other ROC variants are nearly fully penetrant(Trinh et al, 2014), with only a few known examples of individuals greater than 65 years of age that do not have PD.…”
Section: Genetic and Biochemical Support Of A Gain-of-function Incmentioning
confidence: 99%
See 2 more Smart Citations
“…The G2019S mutation in the activation loop of the kinase domain produces a ~3–5 fold effect in some models and clinical samples(Fraser et al, 2016a), and the mutation is well-known to be incompletely penetrant in the Ashkenazi Jewish population (e.g., ~20–30% lifetime risk for PD)(Marder et al, 2015). The Y1699C variant and other ROC variants are nearly fully penetrant(Trinh et al, 2014), with only a few known examples of individuals greater than 65 years of age that do not have PD.…”
Section: Genetic and Biochemical Support Of A Gain-of-function Incmentioning
confidence: 99%
“…It is important to note that while the pSer935 site may reflect LRRK2 kinase inhibition, it is an indirect measure of LRRK2 kinase activity and expected phosphorylation of substrates. So far in model systems, pSer935 has mirrored the dephosphorylation of the LRRK2 substrate pSer1292 and pRab (Fraser et al, 2016a; Henry et al, 2015; Steger et al, 2016). …”
Section: Biomarkers For Lrrk2 Inhibition and Therapeutic Windows Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinase domain that harbors the most common LRRK2 mutation, G2019S, can direct intrinsic phosphorylation (ie, autophosphorylation) in and nearby the GTPase domain . Pathogenic LRRK2 mutations including the R1441C, Y1699C, and G2019S mutations increase autophosphorylated LRRK2 protein levels in model systems . One of the most abundant sites of autophosphorylation is the Ser‐1292 residue near the GTPase domain .…”
mentioning
confidence: 99%
“…Our previous work demonstrated that the LRRK2 protein can be purified from urinary exosomes in biobanked samples . Recently, we discovered that medicated PD patients with the G2019S‐ LRRK2 mutation show a ∼5‐fold elevation of autophosphorylated Ser(P)‐1292 LRRK2 protein in urinary exosomes when compared with noncarrier controls and medicated PD patients without the G0219S‐ LRRK2 mutation . LRRK2 autophosphorylation has not been previously evaluated in a larger series of idiopathic PD cases.…”
mentioning
confidence: 99%